Pengaruh Pemberian Ekstrak Rosela (Hibiscus sabdariffa Linn) dengan Metode Evaporasi Terhadap Kualitas Kimia dan Organoleptik Daging Se'i Kambing - Ramli, Mutiara M.; Sipahelut, Sipahelut; Malelak, Gemini E. (Yayasan Sumber Daya Manusia Cerdas, 2024)
Meat is the part of slaughtered animals that is used as food, apart from having an attractive appearance, it is also a source of high quality animal protein This research was conducted with the aim of knowing the effect of Roselle extract (Hibiscus Sabdariffa) on the quality of goat se'i meat. The method used was the experimental method with a completely randomized design (CRD) consisting of 4 treatments and 4 replications so that there were 16 experimental units. Administration of roselle extract consisted of treatments ER0=0%, ER1=1%, ER2=3%, ER3=5%. The parameters measured in the study were physicochemical tests including protein content, fat content, cholesterol levels, antioxidant activity and organoleptic tests including color, aroma and taste. Statistical test results showed that administration of roselle flower extract had a very significant (P<0.01) effect on cholesterol levels, antioxidant activity, color, aroma and taste, while it had no significant effect (P>0.05) on protein and fat levels. In conclusion, administration of Roselle flower extract using the evaporation method of 5% can increase antioxidant activity, color, aroma and taste of goat se'i meat, while the cholesterol levels, protein content and fat content do not change.